Modeling of sample withdrawal effects on pseudo-order batch sorption kinetics - Adolacion, Jay R T.; Dalida, Maria Lourdes P.
Apparent sorption kinetics determined from single-run batch studies can drift significantly from true kinetics in systems where sorbent quantity remains constant with respect to sample withdrawal. This systematic error is investigated for sorption reaction models, generalized to any reaction order. The problem is formulated to quantify the bias associated with the number and volume of samples withdrawn under relatively slow equilibrium. The results are extended to rapidly equilibrating systems following the Langmuir isotherm model.
Also available in print.
Keywords: Pseudo-order.; Sorption; Kinetics; Equilibrium; Modeling; Bias; Sampling error